HUBUNGAN TINGGI BADAN, INDEKS MASSA TUBUH TRIMESTER SATU DAN KURANG ENERGI KRONIK PADA IBU HAMIL DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS MARGADADI INDRAMAYU - Ayu Nawang Wulan (2023)
Stunting is a nutritional problem in Indonesia. Indramayu is one of the regencies in West Java with a high prevalence of stunting, with 29.19% cases in 2019. Multiple factors may lead to stunting. Mother is a crucial factor that influences the prevalence of stunting. The prevalence of stunting in children is influenced by several maternal factors, including height, first trimester body mass index, and chronic energy insufficiency. This study aims to determine the relationship between height, first trimester body mass index, and chronic energy deficiency in pregnant women with the number of stunting cases in the Puskesmas (Community Health Center) Margadadi Indramayu. This study was quantitative with a cross-sectional approach. The samples used were 44 mothers with stunted children aged 12-59 months in the Community Health Center of Margadadi Indramayu according to the inclusion and exclusion criteria, collected using the consecutive sampling method. The univariate analysis conducted indicated that 23 (53.2%) were short stature, 26 (59.1%) had a no-risk first trimester body mass index, 22 (50%) experienced chronic energy deficiency, and 19 (43.2%) had stunted children with very short category. The bivariate analysis found a relationship between height (p-value = 0.000), first trimester body mass index (p-value = 0.000), chronic energy deficiency (p-value = 0.000), and stunting. Meanwhile, the multivariate analysis indicated that chronic energy deficiency was the most dominant variable in stunting (p-value = 0.005; OR = 35.901; 95% Cl: 3.005 - 428.972). This study proves that short height, first-trimester body mass index are at risk, and chronic energy deficiency can result in stunting in children related to malnutrition in pregnant women.